Large differences in digestibility of crop residues from sorghum varieties - Reed, J.D.; Tedla, A.; Jutzi, S.C. (International Livestock Centre for Africa, 1986)
Presents findings of a study carried out to determine differences between 24 sorghum varieties in digestibility of leaf and stem components and yield of stover. Emphasis is given to encourrage breeds involved in slelecting sorghum varieties for use on small farms where sorghum stover is an important feed resource.